Ação de fármacos nas contrações da musculatura da cérvix de suínos - Padilha Nakaghi, Luciana Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Pharmacological manipulation of cervix has a potentially important role for aiding either artificial insemination or embryo transfer in species requiring surgical procedures to aid conception. By studying basic pharmacological and mechanical properties of the cervix, we aimed with this study to provide a better knowledge about cervical smooth muscle activity and then present and discuss insights into possible drugs for the pig that could facilitate biotechnological procedures for reproduction. Circular (CM) and longitudinal (LM) smooth muscle strips were dissected from porcine uterus (cornu and corpus) and cervix and prepared for isometric tension recording in organ-bath of 20mL of modified Krebs Henseleit solution (pH 7.4) maintained at 37oC and gassed with 95% O2 and 5% CO2. Cervical strips produced larger mechanical responses than the uterine segments, but exhibited less spontaneous activity. All preparations responded in a frequency-dependent manner to electrical field stimulation (EFS, 2Hz-32Hz, 300mA for 30s) with a contraction. Especially in cervix, after neurogenic responses, there was a period of important muscular quiescence until the resume of normal spontaneous activity. In most cervical preparations (CM and LM) atropine abolished neurogenic contractions, highlighting a major role for cholinergic nerves and muscarinic receptors, but a small proportion of preparations exhibited atropine-resistant responses. These responses were not affected by phentolamine, and neither by prazosina and phenylephrine suggesting no role for alpha-adrenoceptors. L-NAME (N-nitro-L-arginina-metil-ester) did not affect the cervical smooth muscle activity, excluding the role of nitric oxide. Diltiazem, papaverine and isoprenaline inhibited neurogenic contractions in CM and LM strips of the cervix, consistent with important roles for voltage-sensitive calcium channels, phosphodiesterase and beta-adrenoceptors, respectively. However, RP73401 ...

A manipulação farmacológica da cérvix possui potencial importante na assistência à biotécnicas da reprodução, como inseminação artificial e transferência de embriões, em espécies que o acesso transcervical ao útero é muito difícil e, portanto, necessitam de procedimento cirúrgico para aumentar as taxas de concepção. Por meio de estudos básicos das propriedades mecânicas e farmacológicas da cérvix, objetivou-se com este estudo fornecer maior conhecimento da atividade da musculatura lisa da cérvix e então apresentar e discutir possibilidades de fármacos que possam relaxá-la e, portanto facilitar a passagem transcervical. Segmentos do músculo liso circular (MC) e longitudinal (ML) foram dissecados do útero (corno e corpo) e cérvix de suínos e preparados para tensão isométrica em banhos de órgão isolados de 20mL de solução modificada de Krebs-Henseleit (pH 7,4) gaseificada com 95% O2: 5% CO2 a 37°C. Os segmentos da cérvix apresentaram maiores respostas mecânicas do que os uterinos, mas exibiram menor atividade espontânea. Todas as preparações responderam de maneira dependente à frequência de estimulação de força elétrica (EFE, 2Hz - 32Hz, 300mA, por 30s). Especialmente na cérvix, após as respostas neurogênicas, houve um período de quiescência muscular importante até que as atividades espontâneas retornassem ao normal. Na maioria das preparações cervicais (MC e ML) a atropina aboliu as contrações neurogênicas, destacando um maior envolvimento para inervação colinérgica e receptores muscarínicos, mas uma pequena proporção das preparações se mostraram resistente à atropina. Estas respostas não foram afetadas pela fentolamina, e nem pela prazosina e fenilefrina, sugerindo a ausência de receptores alfa-adrenérgicos. L-NAME (N-nitro-L-arginina-metil-ester) não teve nenhum efeito sobre a atividade muscular cervical, excluindo o envolvimento de óxido nítrico. Diltiazem...
Keywords: Suino; Colo uterino; Reprodução animal; Relaxamento; Fármacos; Contração muscular; Cervix uteri